2020
DOI: 10.1038/s41598-020-70937-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of canine obesity in the city of São Paulo, Brazil

Abstract: canine obesity is associated with comorbidities, a shortened lifespan, and a poorer quality of life, but epidemiological studies characterizing canine obesity in Latin America are scarce. therefore, this study aimed to determine the prevalence of canine obesity in the city of Sao paulo, Brazil, and the possible associated causal factors. Randomly-selected households from different city regions were visited. Dogs in each household were evaluated and owners completed a questionnaire whilst their anthropometric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 32 publications
0
24
0
14
Order By: Relevance
“…Obesity is defined as the excessive accumulation of adipose tissue in the body [1] and results from a prolonged imbalance between the relative increase in energy consumption and the decrease in energy expenditure, often associated with low physical activity [2]. Several authors have described a high frequency of obesity and overweight in companion animals around the world [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is defined as the excessive accumulation of adipose tissue in the body [1] and results from a prolonged imbalance between the relative increase in energy consumption and the decrease in energy expenditure, often associated with low physical activity [2]. Several authors have described a high frequency of obesity and overweight in companion animals around the world [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary habits of the dog owners might also influence their pets’ diet and risk of adiposity—for example through portion control, frequency of feedings, and whether owners provide table scraps in addition to dog food. 15 16 40 41 The use and timing of dog treats has been associated with the weight of owners, 17 suggesting an interplay between weight of a dog owner and energy intake in the pet. Although it has been assumed that diabetes in dogs has an autoimmune origin because of the insulinopenic presentation, other studies emphasise the heterogeneity of the pathogenesis of diabetes in dogs 7 and have identified obesity as a risk factor for the development of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A larger European cross sectional study based on online questionnaires, however, did not find such an association,39 although that study could have been limited by the owners’ assessment of the body composition of their dog. Dietary habits of the dog owners might also influence their pets’ diet and risk of adiposity—for example through portion control, frequency of feedings, and whether owners provide table scraps in addition to dog food 15164041. The use and timing of dog treats has been associated with the weight of owners,17 suggesting an interplay between weight of a dog owner and energy intake in the pet.…”
Section: Discussionmentioning
confidence: 99%
“…Canine obesity is a complex condition with a high prevalence (around 40% to 50%) among the worldwide population of dogs [ 1 – 5 ]. Overweight is associated with certain diseases, such as orthopedic [ 6 8 ], cardiovascular [ 9 13 ] and respiratory [ 14 17 ], metabolic disorders like insulin and leptin resistance [ 18 , 19 ], hyperlipidemia [ 20 22 ], immunoinflammatory response alterations [ 23 ], and reduced lifespan [ 24 ], which can be partially or completely reversed after weight loss despite reaching ideal body condition score [ 23 ].…”
Section: Introductionmentioning
confidence: 99%